ESTIMASI POTENTIAL LOSS PENERIMAAN PAJAK DARI KEGIATAN UNDERGROUND ECONOMY DENGAN PENDEKATAN MONETER - Tenang Sapardi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2013)
One of the major problems in estimating GDP is the absence of reliable, accurate, timely and consistent official economic and sosial statistics. One of them is that official statistics do not take into account the underground economy when estimating GDP. Deficiencies in estimation techniques and difficulties associated with data collection lead to misreporting and underreporting of national account statistics. The precence of a large underground economy undermines goverment revenue and tax collection. For this reasons, it is crucial to know the size of the underground economy and the magnitude of their activity in order to assess the implications for tax revenues or fiscal revenues. The data consist of quartely observations form 2000-2009 and are taken from BI, BPS and Minister of Finance. Estimating use the currency demand appraach, the first attempt to investigate the size of the underground economy using monetary variabels as a proxy.Keywords: underground economy, monetary approach, currency demand, tax potential loss